A rare case report of iatrogenic Cushing syndrome caused by direct anti-hepatitis C virus therapy with sofosbuvir/velpatasvir. Issue 51 (23rd December 2022) - Ma, Bo; Shang, Tianling; Huang, Jianjie; Tu, Zhixin; Wang, Yan; Han, Yujin; Wang, Yang; Wen, Xiaoyu; Jin, Qinglong
Abstract : Rationale: Sofosbuvir/velpatasvir (SOF/VEL) is a combination of direct-acting antivirals with pan-genotypic activity that is used to treat chronic hepatitis C virus infection. This was a fixed-dose regimen. SOF is a nucleotide nonstructural 5B polymerase inhibitor and VEL is an nonstructural 5A inhibitor. Side effects of this agent on the endocrine system, particularly iatrogenic Cushing syndrome (ICS), are uncommon. Here, we present a case of ICS with significantly low serum adrenocorticotropic hormone and cortisol levels caused by SOF/VEL. Patient concerns: A 49-year-old Asian woman with chronic hepatitis C and cirrhosis presented with a round face, fat thickening at the clavicle and back of the neck, mild facial edema, facial congestion, skin ulceration on the hands, central obesity, acne, and general status changes after 3 months of treatment with SOF/VEL (400 mg/dose, 1/day). Diagnoses: The patient's serum adrenocorticotropic hormone and cortisol levels dropped significantly, and her normal rhythm vanished, with no visible aberrant lesions on computed tomography or across the abdomen. The patient was diagnosed with ICS. Outcomes: Symptoms improved after withdrawing SOF/VEL and taking low-dose oral hydrocortisone. Thus, the SOF/VEL was suspected to be an offender. To our knowledge, this is the first time that SOF/VEL has been linked to ICS. Lessons: Hepatologists and primary care physicians treating hepatitis C virus should be more aware of this uncommon adverse event so that direct-acting antiviral therapy can be stopped sooner if it recurs. The findings of this study emphasize the importance of collaboration between hepatologists and endocrinologists in co-management of complications.